Antibodies from patients with melioidosis recognize Burkholderia mallei but not Burkholderia thailandensis antigens in the indirect hemagglutination assay. - Tiyawisutsri, R; Peacock, S; Langa, S; Limmathurotsakul, D; Cheng, A; Chierakul, W; Chaowagul, W; Day, N; Wuthiekanun, V (2005)
The indirect hemagglutination assay routinely used to detect antibodies to Burkholderia pseudomallei was modified to detect cross-reactivity of antibodies to B. pseudomallei, B. mallei, and B. thailandensis antigens. We demonstrate a lack of cross-reactivity between B. pseudomallei and B. thailandensis but marked cross-reactivity between B. pseudomallei and B. mallei.